C5a/C5aR1 Pathway Is Critical for the Pathogenesis of Psoriasis - Zheng, Quan-you; Liang, Shen-ju; Xu, Feng; Li, Gui-qing; Luo, Na; Wu, Shun; Li, You; Tang, Ming; Zhong, Yu; Chen, Jian; Yang, Di; Sun, Dao-dong; et al. (Frontiers in Immunology, 2019)
Psoriasis is one of the most common chronic inflammatory skin diseases, affecting approximately 2% of the population. The lack of characterization of the pathogenesis of psoriasis has hindered efficient clinical treatment of the disease. In our study, we observed that expression of complement component 5a receptor 1(C5aR1) was significantly increased in skin lesions of both imiquimod (IMQ) and IL23-induced psoriatic mice and patients with psoriasis. C5aR1 deficiency or treatment with C5a receptor antagonist (C5aRa) in mice significantly attenuated psoriasis-like skin lesions and expression of inflammatory cytokines and chemokines. Moreover, C5aR1 deficiency significantly decreased IMQ-induced infiltration of plasmacytoid dendritic cells (pDCs), monocytes and neutrophils in psoriatic skin lesions and functions of pDCs, evidenced by the remarkable reduction in the IMQ-induced production of interferon-α (IFN-α) and tumor necrosis factor α (TNF-α), and FMS-like tyrosine kinase 3 ligand (FLT3L)-dependent pDCs differentiation. Accordingly, in vitro treatment with recombinant C5a accelerated pDCs migration and the differentiation of bone marrow cells into pDCs. Furthermore, biopsies of psoriatic patients showed a dramatic increase of C5aR1+ pDCs infiltration in psoriatic skin lesions, compared to healthy subjects. Our results provide direct evidence that C5a/C5aR1 signaling plays a critical role in the pathogenesis of psoriasis. Inhibition of C5a/C5aR1 pathway is expected to be beneficial in the treatment of patients with psoriasis.